COOPERATION IN THE DEVELOPMENT OF DIGITAL TRANSIT DOCUMENTS, “SINGLE WINDOW” SYSTEMS AND LOGISTICS PARKS (Universal International Scientific Journal, 2026)
This article examines the role of digital transit documents, single window systems, and logistics parks in the development of international economic cooperation and modern logistics infrastructure. In the context of globalization and digital transformation, the implementation of electronic documentation and integrated digital platforms has become an important factor for improving the efficiency of international transport corridors and trade operations. The study analyzes international experience in the application of digital transit documentation and the single window mechanism, emphasizing their contribution to the simplification of customs procedures, reduction of administrative barriers, and acceleration of cross‑border trade processes. Particular attention is paid to the creation and development of logistics parks as integrated infrastructure complexes that combine transport, warehousing, customs, and logistics services within a unified system. The research also highlights the strategic role of regional cooperation in the formation of modern logistics networks. Special consideration is given to Azerbaijan’s geostrategic position and its growing importance as a transport and logistics hub in Eurasia. The article concludes that the integration of digital technologies, coordinated policy measures, and international collaboration are essential for strengthening global supply chains and ensuring sustainable development of transport and logistics systems.
Keywords: digital transit documents, single window system, logistics parks, international cooperation, digitalization, transport corridors, logistics infrastructure